PERBANDINGAN QR CODE STATIS DAN QR CODE DINAMIS DALAM PENGAMBILAN ABSEN PEGAWAI DI LINGKUNGAN UNIVERSITAS BUNG HATTA - Yanuarafi, Arisal (UIN Imam Bonjol Padang, 2023)
This research aims to compare the effectiveness of using Static QR Codes and Dynamic QR Codes in the employee attendance system within the University of Bung Hatta environment. Static QR Codes, which store fixed information, are contrasted with Dynamic QR Codes that generate new codes each time they are scanned. The research methodology involves implementing both types of QR Codes at strategic locations within the university, with data collection encompassing response times, accuracy, and user satisfaction. The results indicate that Dynamic QR Codes excel in terms of security and accuracy, albeit requiring additional effort in implementation. The conclusion drawn from this research is that Dynamic QR Codes are recommended for employee attendance capture in a university setting, providing positive implications for human resource management in educational institutions. This study offers practical guidance for other educational institutions considering the adoption of similar technology.